Parity Early Stage of Marriage with Incidence of Postpartum Depression - Eny Retna Ambarwati; Ria Listiyani (International Journal of Public Health Science (IJPHS), 2014)
Postpartum depression is a condition that may be experienced by women. If it is not addressed properly, it will have a negative impact. Determine the correlation between parity and the early stage of the marriage with the incidence of postpartum depression. This research used analytic observational method with cross sectional approach. The population in this research was postpartum mothers in Maternal Hospital Leonisa. The sampling was done using purposive sampling technique. The data analysis was done with univariate and bivariate analysis using Chi-square.The correlation between parity and the incidence of postpartum depression obtains the result of x2 count of 22.864 and p value of 0.000 with df2 and the significance level of (α) at 5% (0.05) x table at 5.591. Therefore, Ho is rejected and Ha is accepted. The correlation between the early stage of the marriage variable with the incidence of postpartum depression obtains a result of x2 count of 12.965 and p value of 0.000 with df 1, the significance level at 5% (0.05), x table at 3.481, therefore, Ho is rejected and Ha is accepted. There is a correlation between parity and the early stage of the marriage with the incidence of postpartum depression.